The Dark Side of Ecotourism - Fabio Corbisiero (Fuori Luogo, 2022)
Ecotourism represents a segment of nature tourism understood as travel to relatively undisturbed or pristine natural areas, usually natural areas protected by the state. A type of non-mainstream tourism that involves some form of interpretive experience of natural and cultural heritage and positively supports the conservation of natural habitat and territorial communities.